Metamaterial inspired dual port dual circular polarization antenna for small satellite communication system - Norsuzlin Mohd Sahar,; Ahasanul Hoquee,; Touhidul Alama,; Mohammad Tariqul Islam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper presents a dual circular polarized C-band patch antenna for a small satellite communication system The antenna consists of two different annular patch structure with three split ring resonators. The antenna is designed considering space environment and the smallest form of satellite structure. The antenna is fabricated space qualified substrate material Rogers 5880 with overall dimension of 85.22× 48.59 × 1.575 mm3. The antenna achieves circular polarization at 5.1 GHz and 5.2 GHz frequency for port 2 and port 1, respectively. The split ring resonator structures contribute to enhance antenna gain and axial beamwidth. Realized gain of 7.29 dB and 7.33 dB are achieved at 5.1 GHz and 5.2 GHz operating frequency with 3dB axial beamwidth of 170̊ and 153̊ , respectively. Antenna size and performance show that the antenna can be a potential candidate for smooth operation of small satellite communication system.